2016
DOI: 10.1186/s12917-016-0929-8
|View full text |Cite
|
Sign up to set email alerts
|

Plasma markers of inflammation and hemostatic and endothelial activity in naturally overweight and obese dogs

Abstract: BackgroundObesity is one of the most prevalent health problems in the canine population. While haemostatic parameters and markers of endothelial function have been evaluated in various disease conditions in dogs, there are no studies of these markers in canine obesity. This study was designed to evaluate the effect of naturally gained weight excess and obesity on inflammatory, hemostatic and endothelial biomarkers in dogs. A total of 37 overweight and obese dogs were compared with 28 normal weight dogs.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 48 publications
2
20
0
Order By: Relevance
“…This may have contributed to some of the outliers observed within liver histopathologic groups in our study. In addition, obesity is associated with modest increases in IL‐6, CCL2, and CRP in dogs, and could have confounded measurements . Most dogs in our study had BCS of 4–6, with only 1 dog scoring > 7, so obesity was an unlikely cofounder in our study population.…”
Section: Discussionmentioning
confidence: 87%
“…This may have contributed to some of the outliers observed within liver histopathologic groups in our study. In addition, obesity is associated with modest increases in IL‐6, CCL2, and CRP in dogs, and could have confounded measurements . Most dogs in our study had BCS of 4–6, with only 1 dog scoring > 7, so obesity was an unlikely cofounder in our study population.…”
Section: Discussionmentioning
confidence: 87%
“…Recent studies in dogs are shedding some light on the presence of low‐grade inflammation in overweight or obese dogs. As with humans, investigators have observed that IL‐6 and TNF‐α are elevated in obesity‐induced low‐grade inflammation . In addition, there is evidence that T cell proliferative capacity is reduced in dogs in the setting of obesity, although interestingly, no differences in B‐cell responses were observed .…”
Section: Multispecies Evaluation Of Immune‐modifying Effects Of Obesitymentioning
confidence: 98%
“…As with humans, investigators have observed that IL-6 and TNF-are elevated in obesity-induced low-grade inflammation. 61,62 In addition, there is evidence that T cell proliferative capacity is reduced in dogs in the setting of obesity, although interestingly, no differences in B-cell responses were observed. 63 In our laboratory, we have also observed impaired T cell responses to in vitro stimulation in obese vs. lean dogs (BCS > 6 vs. < 4, respectively, manuscript submitted).…”
Section: Dogmentioning
confidence: 99%
“…Importantly, a similar phenotype has been characterized not just in mice and humans, but also canines and non-human primates [1417]. Increases in adipose tissue lead to this inflammatory state, by recruiting different immune cell populations into the adipose tissue, notably macrophages and T cells.…”
Section: Effects Of Obesity On the Immune Systemmentioning
confidence: 99%
“…Nonetheless, defects in thymic function could account for many of the complications with infection and cancer in obese patients. Most studies examining the functional potential of T cells in obesity find defects in their ability to mount effective immune responses in multiple species and models [1417,23,26,27,6466]. On the other hand, some have found enhanced T cell function, leading to exacerbated pathology and disease [67,68].…”
Section: Obesity and T Cell Exhaustionmentioning
confidence: 99%